PERILAKU MEROKOK PADA SANTRI DI PESANTREN ROUDLOTUL FALAH DI DESA SIDOREJO KECAMATAN PAMOTAN KABUPATEN REMBANG - Indartik, Indartik (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
This research is aimed to know the factors which cause smoking behavior on student of Roudlotul Falah Moslem school, and how their smoking behavior: Subject of this research are six students of Roudlotul Falah Moslem School who smoke. Results from interview, observation, documentation, and graphic test (DAM and HTP). The results show the factors which cause smoking behavior of the students are psychological factors (one of way to be consider free and adult person among their friends who smoke, pass the free time, happiness, conformity, and considered manly, less confidence, and also education about disadvantages of smoking for health), environment factors (parental, siblings, peer group), cigarette advertisement, artist of cigarette advertisement, Moslem school regulation factor and society factor. In addition the result also shows that three is a cognitive dissonance in student who smokes. Three is inappropriate between cognition “I 'm a smoker